2017
DOI: 10.1080/15548627.2017.1356550
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide mediates hepatic stellate cell activation by regulating autophagy and retinoic acid signaling

Abstract: Bacterial translocation and lipopolysaccharide (LPS) leakage occur at a very early stage of liver fibrosis in animal models. We studied the role of LPS in hepatic stellate cell (HSC) activation and the underlying mechanisms in vitro and in vivo. Herein, we demonstrated that LPS treatment led to a dramatic increase in autophagosome formation and autophagic flux in LX-2 cells and HSCs, which was mediated through the AKT-MTOR and AMPK-ULK1 pathway. LPS significantly decreased the lipid content, including the lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 50 publications
2
69
0
Order By: Relevance
“…In our study, we found that there was no signi cant difference in the protein expression of TLR4, MyD88, NF-κB and BAMBI between the NC group and DHZCP group, suggesting that DHZCP may not directly target at HSCs. BAMBI was a TGFβ pseudoreceptor that silences TGF-β signaling[30], only one LPS-related gene signi cantly downregulated in 121 gene in HSCs regulated by LPS [3]. In the present study, LPS induced HSC-T6 cells to express TLR4, activated the in ammatory signal pathway, enhanced the activity of NF-κB, and decreased the expression of BAMBI.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…In our study, we found that there was no signi cant difference in the protein expression of TLR4, MyD88, NF-κB and BAMBI between the NC group and DHZCP group, suggesting that DHZCP may not directly target at HSCs. BAMBI was a TGFβ pseudoreceptor that silences TGF-β signaling[30], only one LPS-related gene signi cantly downregulated in 121 gene in HSCs regulated by LPS [3]. In the present study, LPS induced HSC-T6 cells to express TLR4, activated the in ammatory signal pathway, enhanced the activity of NF-κB, and decreased the expression of BAMBI.…”
Section: Discussionmentioning
confidence: 47%
“…Transforming growth factor-β (TGF-β) was powerful brogenic cytokine and HSCs activator [2]. Lipopolysaccharide (LPS),an exogenous Toll-like receptor 4(TLR4) ligand, activated the TLR4-myeloid differentiation factor 88 (MyD88)-nuclear factor-κB (NF-κB) signal in HSCs, and leaded to the decrease of TGF-β pseudo receptor bone morphogenic protein and activin membrane-bound inhibitor (BAMBI) in HSCs [3,4], which made HSCs become more sensitive to TGF-β, that is the main mechanism of endotoxininduced liver brosis.…”
Section: Introductionmentioning
confidence: 99%
“…HEK293 cells (American Type Culture Collection [ATCC], CRL‐1573) and NCI‐H1299 cells (ATCC, CRL‐5803) were cultured in Dulbecco's modified Eagle's medium (DMEM; Cellgro, 10‐013‐CV) supplemented with 10% fetal bovine serum (HyClone, SH30910.03) and 1% penicillin/streptomycin (15140122; Thermo Fisher Scientific, Waltham, MA). Hepatic stellate cells (HSCs) were isolated from mouse liver and cultured as reported previously . The cell purity was determined using glial fibrillary acidic protein (GFAP) immunofluorescence staining.…”
Section: Methodsmentioning
confidence: 99%
“…When autophagy occurs, autophagic lysosomal flux increases to promote dysfunctional organelle, excessive catabolism, misrecognition, or misfolded proteins to metabolize quickly, which then further promotes HSCs activation 21,22 . Recent studies demonstrated that exogenous administration of inflammation inducers lipopolysaccharide (LPS) activated TGF-β1 signaling through promoting autophagy, which aggravated eventually the activation of HSCs 21 . Herein, we aim to search for an appropriate therapy strategy to attenuate hepatic fibrosis through regulating autophagy process and ameliorating chronic inflammation in the liver.…”
Section: Introductionmentioning
confidence: 99%